Potassium ion battery negative electrode material and preparation method and application thereof
Patent Information
- Application Number
- CN202211310419.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-25
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2042-10-25
AI Technical Summary
[0004]然而,K+的阳离子半径大于Li+和Na+,会对离子的储存能力产生不利影响,与此同时,在循环过程中也易引起材料体积膨胀,使循环性能变差
[0016]本发明提供了一种钾离子电池负极材料,通过将磷元素和碳元素均匀分散于多孔五氧化二铌(Nb2O5)的孔隙中,一方面利用五氧化二铌本身能够承受钾离子在脱嵌过程中的应力作用和极低体积膨胀率(小于5%),以及可以进行可逆的吸收钾离子的特点,来保证材料的储钾容量和初始效率;另一方面将五氧化二铌形成多孔骨架结构,可以抑制磷在充放电过程中高的体积膨胀,避免材料粉化,提高电池的循环性能;此外,分散在多孔五氧化二铌孔隙中的磷单质和碳单质,磷具有高比容量,碳具有高导电性,可以使材料保持较高的容量的同时,提高材料整体的导电性能;通过上述五氧化二铌的特性、多孔骨架结构以及高比容量的磷和高导电性的碳,这三方面的协同作用,使本发明提供的钾离子电池负极材料具有较低的体积膨胀率、较高的比容量和较好的循环性能。
Smart Images

Figure CN117976833B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of potassium-ion battery materials technology, and in particular to a potassium-ion battery anode material, its preparation method, and its application. Background Technology
[0002] With the increasing demand for energy in modern society and the large-scale deployment and application of electric vehicles, portable electronic devices, and energy storage technologies, lithium battery development is now facing challenges such as slow improvement in energy density, scarcity of lithium and cobalt resources, and high costs.
[0003] As an alternative to traditional lithium-ion batteries (LIBs), potassium-ion batteries (KIBs) have attracted attention and widespread research interest because they share many similarities with mature LIB technologies in terms of storage mechanisms, electrolyte configuration, and high voltage. Furthermore, potassium resources are abundant and widely distributed, with a content of 1.5 wt% in the Earth's crust (while lithium resources account for only 0.0017%).
[0004] However, K + The cation radius is greater than that of Li + and Na + This can negatively impact the ion storage capacity, and at the same time, it can easily cause material volume expansion during cycling, leading to poor cycle performance. Furthermore, potassium ions migrate slowly, making rapid charge-discharge difficult and resulting in poor rate performance. Therefore, compared to LIBs, KIBs generally exhibit poorer potassium storage capacity, cycle stability, and rate performance. Summary of the Invention
[0005] This invention provides a potassium-ion battery anode material, its preparation method, and its application. By uniformly dispersing phosphorus and carbon elements within the pores of porous niobium pentoxide (Nb₂O₅), the material's potassium storage capacity and initial efficiency are ensured by utilizing niobium pentoxide's ability to withstand stress during potassium ion insertion / extraction, its extremely low volume expansion rate (less than 5%), and its reversible potassium ion absorption. Furthermore, the porous framework structure of niobium pentoxide suppresses the high volume expansion of phosphorus during charge and discharge, preventing material pulverization and improving battery cycle performance. Additionally, the phosphorus and carbon elements dispersed within the porous niobium pentoxide pores, with phosphorus exhibiting high specific capacity and carbon possessing high conductivity, enhance the overall conductivity while maintaining high capacity. Through the synergistic effect of these three aspects, the potassium-ion battery anode material provided by this invention, when applied to potassium-ion batteries, enables the batteries to exhibit characteristics such as low volume expansion rate, high specific capacity, and long cycle life during cycling.
[0006] In a first aspect, embodiments of the present invention provide a potassium-ion battery anode material, the potassium-ion battery anode material comprising: porous niobium pentoxide, phosphorus and carbon; The phosphorus element is uniformly dispersed within the pores of the porous niobium pentoxide; the carbon element is uniformly distributed within the pores and on the outer surface of the porous niobium pentoxide. The pore size of the porous niobium pentoxide is between 1 nm and 500 nm. The porous niobium pentoxide has a particle size Dv50 between 500 nm and 50 μm. The porosity of the porous niobium pentoxide is between 20% and 70%.
[0007] Preferably, the mass percentage of phosphorus in the total mass of the potassium-ion battery anode material is 0.5%-20%. The mass percentage of carbon element in the total mass of the potassium-ion battery anode material is 0.5%-20%.
[0008] Preferably, the potassium-ion battery anode material further includes a carbon coating layer; the mass of the carbon coating layer accounts for 0-20% of the total mass of the potassium-ion battery anode material.
[0009] In a second aspect, embodiments of the present invention provide a method for preparing the potassium-ion battery anode material described in the first aspect above, the method comprising: Preparation of porous niobium pentoxide; Porous niobium pentoxide, phosphorus source material and carbon source material are mixed uniformly in proportion. In an inert atmosphere, the phosphorus source material and the carbon source material are dispersed in the pores of porous niobium pentoxide by one of chemical vapor deposition, liquid phase method or solid phase method to obtain a precursor. The precursor is placed in a high-temperature furnace and subjected to high-temperature heat treatment to obtain the potassium-ion battery anode material.
[0010] Preferably, the method for preparing porous niobium pentoxide specifically involves: carbon coating niobium pentoxide by one of gas phase coating, liquid phase coating, or solid phase coating. After uniformly mixing niobium pentoxide with carbon coating and alkali metal carbonate or alkali metal hydroxide, the mixture is placed in a high-temperature furnace and melted and dispersed at 300℃-1000℃ for 10 min-1 hour. After cooling, it is washed with water, filtered and dried to obtain porous niobium pentoxide. The stirring rate for the melt dispersion is 200 r / min-800 r / min; The porosity of the porous niobium pentoxide is between 20% and 70%.
[0011] Preferably, the phosphorus source material includes one or more of red phosphorus, black phosphorus, blue phosphorus, and purple phosphorus; The carbon source material includes one or more of the following: acetylene, propane, propylene, natural gas, graphene, multi-walled carbon nanotubes, single-walled carbon nanotubes, conductive carbon black, conductive carbon fiber, asphalt, polyvinylidene fluoride, polyvinylpyrrolidone, phenolic resin, and sodium carboxymethyl cellulose.
[0012] Preferably, the high-temperature heat treatment is performed at a temperature of 600℃-1000℃, and the holding time is 1 hour-4 hours.
[0013] Preferably, the preparation method further includes carbon coating treatment of the potassium-ion battery anode material; The carbon coating treatment method includes one of the following: gas phase coating, liquid phase coating, and solid phase coating; The carbon coating layer formed by the carbon coating treatment accounts for 0-20% of the total mass of the potassium-ion battery anode material.
[0014] Thirdly, embodiments of the present invention provide a negative electrode sheet, the negative electrode sheet comprising the potassium-ion battery negative electrode material described in the first aspect above.
[0015] Fourthly, embodiments of the present invention provide a potassium-ion battery, the potassium-ion battery comprising the negative electrode sheet described in the third aspect above.
[0016] This invention provides a potassium-ion battery anode material by uniformly dispersing phosphorus and carbon elements in the pores of porous niobium pentoxide (Nb₂O₅). On one hand, niobium pentoxide itself can withstand the stress of potassium ion insertion / extraction during the process, has an extremely low volume expansion rate (less than 5%), and can reversibly absorb potassium ions, thus ensuring the material's potassium storage capacity and initial efficiency. On the other hand, forming a porous framework structure of niobium pentoxide can suppress the high volume expansion of phosphorus during charge and discharge, preventing material pulverization and improving battery cycle performance. Furthermore, the elemental phosphorus and carbon dispersed in the porous niobium pentoxide pores, with phosphorus having high specific capacity and carbon having high conductivity, can maintain high capacity while improving the overall conductivity of the material. Through the synergistic effect of the characteristics of niobium pentoxide, the porous framework structure, and the high specific capacity of phosphorus and the high conductivity of carbon, the potassium-ion battery anode material provided by this invention exhibits a low volume expansion rate, high specific capacity, and good cycle performance.
[0017] The present invention provides a potassium-ion battery anode material that can be used as an anode active material to prepare anode sheets and applied in potassium-ion batteries, giving potassium-ion batteries high potassium storage capacity, good cycle stability and rate performance. Attached Figure Description
[0018] The technical solutions of the embodiments of the present invention will be further described in detail below with reference to the accompanying drawings and examples.
[0019] Figure 1 This is a flowchart of the preparation of potassium-ion battery anode materials provided in the embodiments of the present invention; Figure 2 These are cycle curves of a full cell assembled with the potassium-ion battery anode material provided in Example 1 of the present invention and a full cell assembled with the phosphorus / carbon composite anode material in Comparative Example 1. Detailed Implementation
[0020] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. However, it should be understood that these embodiments are only for more detailed description and should not be construed as limiting the present invention in any way, that is, not intended to limit the scope of protection of the present invention.
[0021] This invention provides a potassium-ion battery anode material comprising: porous niobium pentoxide, phosphorus, and carbon.
[0022] The porous niobium pentoxide has a pore size between 1 nm and 500 nm, preferably between 10 nm and 400 nm; a particle size Dv50 between 500 nm and 50 μm, preferably between 500 nm and 10 μm; and a porosity between 20% and 70%, preferably between 40% and 65%.
[0023] Phosphorus is uniformly dispersed in the pores of porous niobium pentoxide, and the mass percentage of phosphorus in the total mass of the potassium-ion battery anode material is 0.5%-20%, preferably 7%-17%.
[0024] Carbon is uniformly distributed within the pores and on the outer surface of the porous niobium pentoxide; The mass percentage of carbon in the total mass of the potassium-ion battery anode material is 0.5%-20%, preferably 1%-10%.
[0025] In an optional embodiment, the potassium-ion battery anode material also includes a carbon coating layer; the mass of the carbon coating layer accounts for 0-20% of the total mass of the potassium-ion battery anode material, preferably 0.5%-8%.
[0026] This invention provides a method for preparing the above-mentioned potassium-ion battery anode material, such as... Figure 1 As shown, the specific preparation steps include: Step 110: Prepare porous niobium pentoxide; Specifically, the method for preparing porous niobium pentoxide is as follows: (1) Niobium pentoxide is carbon coated by one of the following methods: gas phase coating, liquid phase coating or solid phase coating; (2) After uniformly mixing niobium pentoxide with carbon coating and alkali metal carbonate or alkali metal hydroxide, the mixture is placed in a high-temperature furnace and melt-dispersed at 300℃-1000℃ for 10min-1 hour. After cooling, it is washed with water, filtered, and dried to obtain porous niobium pentoxide; wherein the stirring rate for melting and dispersion is 200r / min-800r / min; In this step, after niobium pentoxide is treated with carbon, a carbon coating layer is formed locally on its surface. The areas not coated with carbon react with alkali metal carbonates or alkali metal hydroxides during the melting and dispersion process to form pores. Thus, porous niobium pentoxide with a partially carbon-coated surface is prepared, with a porosity between 20% and 70%, preferably 40% to 65%.
[0027] Step 120: Mix porous niobium pentoxide, phosphorus source material and carbon source material uniformly in proportion, and disperse the phosphorus source material and carbon source material in the pores of porous niobium pentoxide in an inert atmosphere by chemical vapor deposition, liquid phase method or solid phase method to obtain the precursor. Among them, phosphorus source materials include one or more of the following: red phosphorus, black phosphorus, blue phosphorus, and purple phosphorus; Carbon source materials include one or more of the following: acetylene, propane, propylene, natural gas, graphene, multi-walled carbon nanotubes, single-walled carbon nanotubes, conductive carbon black, conductive carbon fiber, pitch, polyvinylidene fluoride, polyvinylpyrrolidone, phenolic resin, and sodium carboxymethyl cellulose.
[0028] Step 130: The precursor is placed in a high-temperature furnace and subjected to high-temperature heat treatment to obtain potassium-ion battery anode material. The high-temperature heat treatment temperature is 600℃-1000℃, and the holding time is 1 hour-4 hours.
[0029] In an optional embodiment, the above preparation method further includes carbon coating treatment of the potassium-ion battery anode material; wherein, the carbon coating treatment method includes one of gas phase coating, liquid phase coating, and solid phase coating; the mass of the carbon coating layer formed by the carbon coating treatment accounts for 0-20% of the total mass of the potassium-ion battery anode material, preferably 0.5%-8%.
[0030] The potassium-ion battery anode material prepared by the above preparation method in this embodiment of the invention can be used as an anode active material in the anode sheet. The anode sheet can be applied to potassium-ion batteries, wherein the potassium-ion batteries include, but are not limited to, liquid, semi-solid, and all-solid lithium-ion batteries.
[0031] To better understand the technical solution provided by this invention, the following examples illustrate the preparation method and characteristics of the potassium-ion battery anode material of this invention.
[0032] Example 1 This embodiment provides a method for preparing and testing the performance of a potassium-ion battery anode material. The specific process is as follows: 1) Place 2 kg of niobium pentoxide in a rotary furnace and heat it to 900 °C under a protective atmosphere. Then, introduce argon and acetylene gas at a volume ratio of 2.5:1 for gas phase coating. After holding at this temperature for 90 min, turn off the organic gas source and discharge the material after cooling to room temperature. The carbon-coated niobium pentoxide is obtained, and the carbon content is 1.9% as determined by a carbon-sulfur analyzer. 2) The carbon-coated niobium pentoxide obtained above was mixed evenly with 1.3 kg of sodium carbonate and placed in a high-temperature furnace. It was melted and dispersed at 900°C for 20 min with a stirring rate of 200 r / min. After cooling, it was washed with water, filtered, and dried to obtain porous niobium pentoxide. The porosity of the porous niobium pentoxide was measured to be 21% using a mercury porosimeter. 3) The porous niobium pentoxide obtained above was placed in a ball mill with 1 kg of black phosphorus and 360 g of conductive carbon black. Under an argon atmosphere, the speed was set to 800 r / min, with forward and reverse rotation, and the milling was carried out for 20 hours to disperse the black phosphorus and conductive carbon black in the pores of the porous niobium pentoxide, thus obtaining the precursor.
[0033] 4) The precursor is placed in a high-temperature furnace and heated to 700°C under a nitrogen atmosphere. It is then held at that temperature for 2 hours for high-temperature heat treatment. After discharge, the material is crushed and sieved to obtain potassium-ion battery anode material.
[0034] 5) Carbon coating of the potassium-ion battery anode material prepared in this embodiment: 1 kg of potassium-ion battery anode material is placed in a rotary kiln and heated to 800°C under a protective atmosphere. Argon and acetylene gas are introduced in a volume ratio of 1:1 for gas phase coating. After holding at the temperature for 1 hour, the organic gas source is turned off. After cooling to room temperature, the material is discharged and graded to obtain the potassium-ion battery anode material with carbon coating.
[0035] The negative electrode sheet was prepared using the potassium-ion battery negative electrode material with carbon coating prepared in this embodiment, and coin half-cells and full cells were assembled for testing.
[0036] Preparation method of button half cell: The potassium-ion battery negative electrode material with carbon coating, conductive additive carbon black and binder polyvinylidene fluoride (PVDF) are weighed at a mass ratio of 7:2:1. At room temperature, the mixed materials and solvent N-methylpyrrolidone (NMP) are put into a pulper to prepare a slurry. Then, the slurry is coated on copper foil, dried and cut into pieces. In a glove box, with potassium metal as the counter electrode, glass fiber membrane as the separator, and 0.8M potassium hexafluorophosphate (dissolved in ethylene carbonate / diethyl carbonate (EC / DMC) at a volume ratio of 1:1) as the electrolyte, a button half cell is assembled.
[0037] Test method for button half-cells: The prepared button half-cells were tested in constant current charge and discharge mode using a charge and discharge instrument. The discharge cutoff voltage was 0.01V and the charging cutoff voltage was 3V. The first charge and discharge capacity and initial efficiency performance were tested. The test data are shown in Table 1.
[0038] Preparation and testing of full cells: Preparation of the negative electrode sheet: A composite material containing a carbon-coated potassium-ion battery negative electrode layer and graphite is prepared into a specific capacity of 450 mAh / g. This composite is then weighed and mixed with conductive additive carbon black and binder PVDF at a mass ratio of 7:2:1. At room temperature, the mixed material and solvent NMP are placed in a slurry mixer to prepare a slurry. The prepared slurry is then uniformly coated onto copper foil at a coating speed between 2.2 m / min and 3.5 m / min, with the coating machine's drying tunnel temperature between 70℃ and 100℃. After double-sided drying in the coating machine, the negative electrode sheet is obtained.
[0039] Preparation of the positive electrode: Weigh out the positive electrode material potassium ferrous cyanide (KFe) in a mass ratio of 8:1:1. 2+ [Fe 3+ [CN]6] Conductive additive carbon black and binder PVDF are mixed; at room temperature, the mixed materials and solvent NMP are put into a pulping machine to prepare a slurry; the prepared slurry is uniformly coated on aluminum foil at a coating speed of 2.0m / min-3.0m / min and the baking track temperature of the coating machine is 90-120℃; after double-sided coating and drying by the coating machine, a positive electrode sheet is obtained.
[0040] Battery fabrication: The positive electrode of the positive electrode sheet is exposed using aluminum tabs, and the negative electrode sheet is exposed using copper-plated nickel tabs. The prepared positive and negative electrodes and separator are wound into a bare cell. The cell is then encapsulated with aluminum-plastic film using a heat-sealing process. High-temperature vacuum baking is used to remove moisture from the battery. Then, 1 mole of electrolyte is injected. The electrolyte is a mixed solution of KPF6 and ethylene carbonate / dimethyl carbonate (EC / DMC, volume ratio 1:1). After vacuum sealing, the battery is obtained.
[0041] Testing: Constant current charge and discharge mode tests were conducted using a charge and discharge tester. The discharge cutoff voltage was 2.0V and the charging cutoff voltage was 4.5V. Discharge tests after the first week were all conducted at a 3C current density.
[0042] Electrode expansion rate test: Under 3C conditions, after 300 cycles of full charge, five battery groups were removed, and their negative electrode sheets were taken. The thickness of each electrode sheet was measured at 10 different locations using a thickness gauge, and the average value was taken. Under the same test conditions, the average thickness of the electrode sheet in its initial state was obtained.
[0043] The calculation formula is: Electrode full charge expansion rate = (Average thickness of electrode with different number of turns when fully charged - Initial average thickness of electrode) / Initial average thickness of electrode.
[0044] The results of the cycle retention rate test and the electrode expansion rate test at 3C rate for the full cell prepared in this embodiment after 100 and 300 cycles are detailed in Table 1.
[0045] The cycle curve of the full cell assembled with the potassium-ion battery anode material provided in Embodiment 1 of this invention is shown in the figure below. Figure 2 As shown.
[0046] Example 2 This embodiment provides a method for preparing and testing the performance of a potassium-ion battery anode material. The specific process is as follows: 1) Place 2 kg of niobium pentoxide in a rotary furnace and heat it to 960°C under a protective atmosphere. Introduce argon and propylene gas at a volume ratio of 3:1 for gas phase coating. After holding at this temperature for 120 min, turn off the organic gas source and discharge the material after cooling to room temperature to obtain niobium pentoxide with a carbon coating layer. The carbon content was tested using a carbon-sulfur analyzer and found to be 2.3%. 2) The carbon-coated niobium pentoxide obtained above was mixed evenly with 1 kg of potassium hydroxide and placed in a high-temperature furnace. It was melted and dispersed at 450°C for 40 min with a stirring rate of 500 r / min. After cooling, it was washed with water, filtered, and dried to obtain porous niobium pentoxide. The porosity of the porous niobium pentoxide was measured to be 33% using a mercury porosimeter. 3) The porous niobium pentoxide obtained above was placed in a disperser with 1.2 kg of red phosphorus, 200 g of single-walled carbon nanotubes and water. The dispersion disc of the disperser was set to a speed of 1500 r / min and stirred thoroughly at room temperature for 6 hours to disperse black phosphorus and conductive carbon black in the pores of the porous niobium pentoxide, thus obtaining the precursor slurry.
[0047] 4) The precursor slurry is placed in a high-temperature furnace and heated to 600°C under a nitrogen atmosphere. It is then held at that temperature for 4 hours for high-temperature heat treatment. After discharge, the material is crushed and sieved to obtain potassium-ion battery anode material.
[0048] 5) Carbon coating of the potassium-ion battery anode material prepared in this embodiment: 1 kg of potassium-ion battery anode material was placed in a rotary kiln and heated to 900°C under a protective atmosphere. Argon gas mixed with acetylene and propane was introduced at a volume ratio of 1:2 for gas phase coating, wherein the volume ratio of acetylene and propane was 1:1. After holding at the temperature for 90 min, the organic gas source was turned off. After cooling to room temperature, the material was discharged and graded to obtain the potassium-ion battery anode material with a carbon coating layer.
[0049] The negative electrode sheet was prepared using the potassium-ion battery negative electrode material with a carbon coating layer prepared in this embodiment, and coin half-cells and full cells were assembled for testing. The specific process was the same as in Example 1. The test data are detailed in Table 1.
[0050] Example 3 This embodiment provides a method for preparing and testing the performance of a potassium-ion battery anode material. The specific process is as follows: 1) 2.5 kg of niobium pentoxide was mixed with asphalt emulsion at a mass ratio of 23:1 and stirred for 4 hours to form a uniform slurry. After drying the slurry, it was placed in a rotary kiln and heated to 900℃ under a protective argon atmosphere for 80 minutes. After cooling to room temperature, the material was discharged to obtain niobium pentoxide with a carbon coating. The carbon content was tested using a carbon-sulfur analyzer and found to be 2.1%. 2) The carbon-coated niobium pentoxide obtained above was mixed evenly with 1.1 kg of potassium carbonate and placed in a high-temperature furnace. It was melted and dispersed at 950°C for 30 min with a stirring rate of 300 r / min. After cooling, it was washed with water, filtered, and dried to obtain porous niobium pentoxide. The porosity of the porous niobium pentoxide was measured to be 42% using a mercury porosimeter. 3) The porous niobium pentoxide obtained above was mixed evenly with 1.3 kg of blue phosphorus and 320 g of graphene, and placed in a ball mill. Under an argon atmosphere, the speed was set to 1000 r / min, with forward and reverse rotation, and the ball milling was carried out for 16 hours to disperse the blue phosphorus and graphene in the pores of the porous niobium pentoxide, thus obtaining the precursor.
[0051] 4) The precursor is placed in a high-temperature furnace and heated to 750°C under a nitrogen atmosphere. It is then held at that temperature for 3 hours for high-temperature heat treatment. After discharge, the material is crushed and sieved to obtain potassium-ion battery anode material.
[0052] 5) Carbon coating of the potassium-ion battery anode material prepared in this embodiment: 1 kg of potassium-ion battery anode material and asphalt emulsion are mixed at a mass ratio of 28:1 and stirred for 4 hours to form a uniform slurry. After drying the slurry, it is placed in a rotary kiln and heated to 950°C under a protective atmosphere for 1.5 hours. After cooling and grading, the potassium-ion battery anode material with carbon coating is obtained.
[0053] The negative electrode sheet was prepared using the potassium-ion battery negative electrode material with a carbon coating layer prepared in this embodiment, and coin half-cells and full cells were assembled for testing. The specific process was the same as in Example 1. The test data are detailed in Table 1.
[0054] Example 4 This embodiment provides a method for preparing and testing the performance of a potassium-ion battery anode material. The specific process is as follows: 1) Dissolve 2 kg of niobium pentoxide and phenolic resin in tetrahydrofuran at a mass ratio of 19:1, stir for 6 hours to form a uniform slurry, dry the slurry and place it in a rotary kiln, heat to 970℃ under a protective atmosphere and hold for 2 hours, cool to room temperature and discharge to obtain niobium pentoxide with a carbon coating. The carbon content was tested with a carbon-sulfur analyzer and found to be 2.5%. 2) The carbon-coated niobium pentoxide obtained above was mixed evenly with 1.5 kg of sodium hydroxide and placed in a high-temperature furnace. It was melted and dispersed at 500°C for 50 min with a stirring rate of 500 r / min. After cooling, it was washed with water, filtered, and dried to obtain porous niobium pentoxide. The porosity of the porous niobium pentoxide was tested using a mercury porosimeter and found to be 59%. 3) The porous niobium pentoxide obtained above is mixed evenly with 1.3 kg of purple phosphorus and placed in a vacuum reactor. The vacuum is drawn to 60 Pa, and the temperature is raised to 900 °C. Acetylene gas is introduced at a flow rate of 2 L / min and kept at the temperature for 2 hours to disperse the purple phosphorus and carbon elements in the pores of the porous niobium pentoxide. After discharge, the material is crushed and sieved to obtain the potassium-ion battery anode material.
[0055] 4) Carbon coating of the potassium-ion battery anode material prepared in this embodiment: 1 kg of potassium-ion battery anode material and phenolic resin were dissolved in tetrahydrofuran at a ratio of 26:1 and stirred for 3 hours to form a uniform slurry. After drying the slurry, it was placed in a rotary kiln and heated to 970°C for 2 hours under a protective atmosphere. After cooling and grading, the potassium-ion battery anode material with carbon coating was obtained.
[0056] The negative electrode sheet was prepared using the potassium-ion battery negative electrode material with a carbon coating layer prepared in this embodiment, and coin half-cells and full cells were assembled for testing. The specific process was the same as in Example 1. The test data are detailed in Table 1.
[0057] Example 5 This embodiment provides a method for preparing and testing the performance of a potassium-ion battery anode material. The specific process is as follows: 1) Place 2 kg of niobium pentoxide in a rotary furnace and heat it to 1000℃ under nitrogen. Then, introduce argon, propane, and natural gas in a volume ratio of 3:1:1 for gas phase coating. After holding at this temperature for 100 min, turn off the organic gas source and discharge the material after cooling to room temperature. This yields niobium pentoxide with a carbon coating layer. The carbon content was measured to be 1.5% using a carbon-sulfur analyzer. 2) The carbon-coated niobium pentoxide obtained above was mixed evenly with 800g of lithium carbonate and placed in a high-temperature furnace. It was melted and dispersed at 700℃ for 10min with a stirring rate of 300r / min. After cooling, it was washed with water, filtered, and dried to obtain porous niobium pentoxide. The porosity of the porous niobium pentoxide was tested using a mercury porosimeter and found to be 25%. 3) The porous niobium pentoxide obtained above was placed in a ball mill with 1 kg of black phosphorus, 340 g of multi-walled carbon nanotubes and anhydrous ethanol. Under a nitrogen atmosphere, the speed was set to 1500 r / min, and the milling was carried out in both forward and reverse directions for 15 hours to disperse the black phosphorus and conductive carbon black in the pores of the porous niobium pentoxide, thus obtaining the precursor slurry.
[0058] 4) The precursor slurry is placed in a high-temperature furnace and heated to 700°C under a nitrogen atmosphere. It is then held at that temperature for 3 hours for high-temperature heat treatment. After discharge, the material is crushed and sieved to obtain potassium-ion battery anode material.
[0059] The negative electrode sheet was prepared using the carbon-free potassium-ion battery negative electrode material prepared in this embodiment, and coin half-cells and full cells were assembled for testing. The specific process was the same as in Example 1. The test data are detailed in Table 1.
[0060] Example 6 This embodiment provides a method for preparing and testing the performance of a potassium-ion battery anode material. The specific process is as follows: 1) Mix 2.5 kg of niobium pentoxide with petroleum asphalt at a mass ratio of 18:1, place in a high-temperature furnace, heat to 850°C under a protective atmosphere, hold at that temperature for 1.5 hours, cool to room temperature, and then discharge and classify to obtain niobium pentoxide with a carbon coating. The carbon content was tested using a carbon-sulfur analyzer and found to be 2.9%. 2) The carbon-coated niobium pentoxide obtained above was mixed evenly with 700g of lithium hydroxide and placed in a high-temperature furnace. It was melted and dispersed at 500℃ for 60min with a stirring rate of 200r / min. After cooling, it was washed with water, filtered, and dried to obtain porous niobium pentoxide. The porosity of the porous niobium pentoxide was measured to be 39% using a mercury porosimeter. 3) The porous niobium pentoxide obtained above is mixed evenly with 1.3 kg of red phosphorus and 850 g of sodium carboxymethyl cellulose, placed in a ball mill, and ball milled for 20 hours under an argon atmosphere at a speed of 700 r / min, with forward and reverse rotation, so that the red phosphorus and sodium carboxymethyl cellulose are dispersed in the pores of the porous niobium pentoxide to obtain the precursor.
[0061] 4) The precursor is placed in a high-temperature furnace and heated to 870°C under a nitrogen atmosphere. It is then held at that temperature for 2.5 hours for high-temperature heat treatment. After discharge, the material is crushed and sieved to obtain potassium-ion battery anode material.
[0062] The negative electrode sheet was prepared using the carbon-free potassium-ion battery negative electrode material prepared in this embodiment, and coin half-cells and full cells were assembled for testing. The specific process was the same as in Example 1. The test data are detailed in Table 1.
[0063] Example 7 This embodiment provides a method for preparing and testing the performance of a potassium-ion battery anode material. The specific process is as follows: 1) Place 2 kg of niobium pentoxide in a rotary furnace and heat it to 890°C under argon conditions. Then, introduce argon and propylene at a volume ratio of 3:1 for gas phase coating. After holding at this temperature for 90 min, turn off the organic gas source and discharge the material after cooling to room temperature to obtain niobium pentoxide with a carbon coating layer. The carbon content was tested using a carbon-sulfur analyzer and found to be 2.2%. 2) The carbon-coated niobium pentoxide obtained above was mixed evenly with 2 kg of potassium carbonate and placed in a high-temperature furnace. It was melted and dispersed at 300°C for 45 min with a stirring rate of 300 r / min. After cooling, it was washed with water, filtered, and dried to obtain porous niobium pentoxide. The porosity of the porous niobium pentoxide was measured to be 67% using a mercury porosimeter. 3) The porous niobium pentoxide obtained above is mixed evenly with 1 kg of blue phosphorus and placed in a vacuum reactor. The reactor is evacuated to 100 Pa and heated to 700 °C. A mixture of propylene and natural gas with a volume ratio of 2:1 is introduced at a flow rate of 5 L / min and kept at this temperature for 1.5 hours to disperse the blue phosphorus and carbon in the pores of the porous niobium pentoxide. After discharge, the mixture is crushed and sieved to obtain the potassium-ion battery anode material.
[0064] 4) Carbon coating of the potassium-ion battery anode material prepared in this embodiment: 1 kg of potassium-ion battery anode material was placed in a rotary kiln and heated to 1000°C under a protective atmosphere. Argon and propylene gas were introduced at a volume ratio of 3:2.5 for gas phase coating. The temperature was maintained for 2 hours and the organic gas source was turned off. After cooling to room temperature, the material was discharged and graded. After cooling and grading, the potassium-ion battery anode material with carbon coating layer was obtained.
[0065] The negative electrode sheet was prepared using the potassium-ion battery negative electrode material with a carbon coating layer prepared in this embodiment, and coin half-cells and full cells were assembled for testing. The specific process was the same as in Example 1. The test data are detailed in Table 1.
[0066] Example 8 This embodiment provides a method for preparing and testing the performance of a potassium-ion battery anode material. The specific process is as follows: 1) 2.3 kg of niobium pentoxide was mixed with polyvinylpyrrolidone at a mass ratio of 24:1, placed in a high-temperature furnace, heated to 800°C under a protective atmosphere, held for 3 hours, cooled to room temperature, and then discharged and graded to obtain niobium pentoxide with a carbon coating. The carbon content was tested using a carbon-sulfur analyzer and found to be 2.0%. 2) The carbon-coated niobium pentoxide obtained above was mixed evenly with 3 kg of potassium hydroxide and placed in a high-temperature furnace. It was melted and dispersed at 600℃ for 50 min with a stirring rate of 300 r / min. After cooling, it was washed with water, filtered, and dried to obtain porous niobium pentoxide. The porosity of the porous niobium pentoxide was tested using a mercury porosimeter and found to be 53%. 3) The porous niobium pentoxide obtained above is mixed evenly with 1.3 kg of purple phosphorus and 1 kg of polyvinylpyrrolidone, placed in a ball mill, and ball milled for 24 hours under an argon atmosphere at a speed of 900 r / min, with forward and reverse rotation, so that the purple phosphorus and polyvinylpyrrolidone are dispersed in the pores of the porous niobium pentoxide to obtain the precursor.
[0067] 4) The precursor is placed in a high-temperature furnace and heated to 750°C under a nitrogen atmosphere. It is then held at that temperature for 4 hours for high-temperature heat treatment. After discharge, the material is crushed and sieved to obtain potassium-ion battery anode material.
[0068] 5) Carbon coating of the potassium-ion battery anode material prepared in this embodiment: 1 kg of potassium-ion battery anode material is mixed with polyvinylpyrrolidone at a mass ratio of 23:1, placed in a high-temperature furnace, heated to 1050°C under a protective atmosphere, kept at that temperature for 2 hours, and then discharged and graded after cooling to room temperature to obtain the potassium-ion battery anode material with carbon coating.
[0069] The negative electrode sheet was prepared using the potassium-ion battery negative electrode material with a carbon coating layer prepared in this embodiment, and coin half-cells and full cells were assembled for testing. The specific process was the same as in Example 1. The test data are detailed in Table 1.
[0070] To better illustrate the effects of the embodiments of the present invention, Comparative Examples 1-2 are compared with the above embodiments.
[0071] Comparative Example 1 This comparative example provides a preparation process and performance testing of a phosphorus / carbon composite anode material. The specific preparation process is as follows: After mixing 1 kg of black phosphorus and 2 kg of graphene evenly, the mixture was placed in a ball mill and milled for 24 hours under an argon atmosphere at a speed of 900 r / min, with both forward and reverse rotation, to obtain the black phosphorus / graphene composite.
[0072] The phosphorus / graphene composite prepared in this embodiment was used to prepare the negative electrode sheet, and a coin cell was assembled for testing. The specific process was the same as in Example 1. The test data are detailed in Table 1.
[0073] The cycle curve of the full cell assembled with the phosphorus / carbon composite anode material in Comparative Example 1 is shown below. Figure 2 As shown in the figure, it can be seen that from about 25 cycles to 300 cycles, the cycle capacity retention rate of the full battery in Comparative Example 1 is significantly lower than that of the full battery in Example 1, indicating that the full battery in Example 1 has better cycle performance.
[0074] Comparative Example 2 This comparative example provides a preparation process and performance testing of a phosphorus / niobium pentoxide composite anode material. The specific preparation process is as follows: 1) Mix 1.5 kg of black phosphorus and 3 kg of niobium pentoxide evenly, place them in a ball mill, and under an argon atmosphere, set the rotation speed to 1200 r / min, and perform forward and reverse rotation for 18 hours to obtain the black phosphorus / niobium pentoxide composite.
[0075] The negative electrode sheet was prepared using the phosphorus / niobium pentoxide composite material prepared in this embodiment, and a coin cell was assembled for testing. The specific process was the same as in Example 1. The test data are detailed in Table 1.
[0076] The initial efficiency and reversible capacity of the negative electrode materials in Examples 1-8 and Comparative Examples 1-2 were tested, as well as the cycle retention rate after 100 and 300 full-charge cycles and the expansion rate of the negative electrode sheet after 300 cycles. The test results are shown in Table 1.
[0077] Table 1 As can be seen from the test data in Table 1, the cycle capacity retention rate and the expansion rate of the negative electrode after 300 cycles of the full cells in Examples 1-8 are significantly better than those of the negative electrode in Comparative Examples 1-2. This is because Examples 1-8, by uniformly dispersing phosphorus and carbon elements in the pores of porous niobium pentoxide (Nb2O5), utilize the inherent properties of niobium pentoxide—its ability to withstand the stress of potassium ion insertion / extraction during the process, its extremely low volume expansion rate (less than 5%), and its reversible absorption of potassium ions—to ensure the material's reversible capacity and initial efficiency. Furthermore, by uniformly dispersing phosphorus and carbon elements in the pores of porous niobium pentoxide... Niobium forms a porous framework structure, which can suppress the high volume expansion of phosphorus during charging and discharging, avoid material pulverization, and improve the cycle performance of the battery. In addition, the phosphorus and carbon elements dispersed in the porous niobium pentoxide pores, with phosphorus having high specific capacity and carbon having high conductivity, can improve the overall conductivity of the material while maintaining high capacity. Through the synergistic effect of the above three aspects, when the potassium-ion battery anode material provided by the present invention is applied to potassium-ion batteries, the potassium-ion batteries can have characteristics such as low volume expansion rate, high specific capacity, and long cycle life during cycling.
[0078] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A potassium-ion battery anode material, characterized in that, The potassium-ion battery anode material includes: porous niobium pentoxide, elemental phosphorus, and elemental carbon; The phosphorus and carbon are uniformly dispersed within the pores of the porous niobium pentoxide; the potassium-ion battery anode material also includes a carbon coating layer. The pore size of the porous niobium pentoxide is between 1 nm and 500 nm. The porous niobium pentoxide has a particle size Dv50 between 500 nm and 50 μm. The porosity of the porous niobium pentoxide is between 20% and 70%. The method for preparing the porous niobium pentoxide is as follows: Niobium pentoxide is carbon coated by one of the following methods: gas phase coating, liquid phase coating or solid phase coating; the carbon-coated niobium pentoxide is mixed evenly with an alkali metal carbonate or an alkali metal hydroxide, and then placed in a high-temperature furnace and melt-dispersed at a temperature of 300℃-1000℃ for 10 min-1 hour. After cooling, it is washed with water, filtered and dried to obtain the porous niobium pentoxide.
2. The potassium-ion battery anode material according to claim 1, characterized in that, The mass percentage of elemental phosphorus in the total mass of the potassium-ion battery anode material is 0.5%-20%. The mass percentage of the carbon element in the carbon element and the carbon coating layer is 0.5%-20% of the total mass of the potassium-ion battery anode material.
3. The potassium-ion battery anode material according to claim 1, characterized in that, The mass of the carbon coating layer accounts for 0.5%-20% of the total mass of the potassium-ion battery anode material.
4. A method for preparing the potassium-ion battery anode material according to any one of claims 1-3, characterized in that, The preparation method includes: Preparation of porous niobium pentoxide; Porous niobium pentoxide, phosphorus source material and carbon source material are mixed uniformly in proportion. In an inert atmosphere, the phosphorus source material and the carbon source material are dispersed in the pores of porous niobium pentoxide by one of chemical vapor deposition, liquid phase method or solid phase method to obtain a precursor. The precursor is placed in a high-temperature furnace and subjected to high-temperature heat treatment to obtain the potassium-ion battery anode material.
5. The preparation method according to claim 4, characterized in that, The method for preparing porous niobium pentoxide specifically involves carbon coating niobium pentoxide by one of gas phase coating, liquid phase coating, or solid phase coating. After uniformly mixing niobium pentoxide with carbon coating and alkali metal carbonate or alkali metal hydroxide, the mixture is placed in a high-temperature furnace and melted and dispersed at 300℃-1000℃ for 10 min-1 hour. After cooling, it is washed with water, filtered and dried to obtain porous niobium pentoxide. The stirring rate for the melt dispersion is 200 r / min-800 r / min; The porosity of the porous niobium pentoxide is between 20% and 70%.
6. The preparation method according to claim 4, characterized in that, The phosphorus source material includes one or more of the following: red phosphorus, black phosphorus, blue phosphorus, and purple phosphorus; The carbon source material includes one or more of the following: acetylene, propane, propylene, natural gas, graphene, multi-walled carbon nanotubes, single-walled carbon nanotubes, conductive carbon black, conductive carbon fiber, asphalt, polyvinylidene fluoride, polyvinylpyrrolidone, phenolic resin, and sodium carboxymethyl cellulose.
7. The preparation method according to claim 4, characterized in that, The high-temperature heat treatment is performed at a temperature of 600℃-1000℃, and the holding time is 1 hour-4 hours.
8. The preparation method according to claim 4, characterized in that, The preparation method further includes carbon coating treatment of the potassium-ion battery anode material; The carbon coating treatment method includes one of the following: gas phase coating, liquid phase coating, and solid phase coating; The carbon coating layer formed by the carbon coating treatment accounts for 0.5%-20% of the total mass of the potassium-ion battery anode material.
9. A negative electrode sheet, characterized in that, The negative electrode sheet includes the potassium-ion battery negative electrode material as described in any one of claims 1-3.
10. A potassium-ion battery, characterized in that, The potassium-ion battery includes the negative electrode sheet as described in claim 9.
Citation Information
Patent Citations
Synthesizing method of modified columbic anhydride for lithium ion battery
CN102593441A
Red phosphorus / nitrogen-doped graphene composite negative electrode material, method for preparing same and application of red phosphorus / nitrogen-doped graphene composite negative electrode material
CN108376767A